Cees Meijer, Jan de Quay (1901-1985). Een biografie - Jan Willem Brouwer (BMGN: Low Countries Historical Review, 2015)
Cees Meijer, Jan de Quay (1901-1985). Een biografie (Amsterdam: Boom, 2014, 512 pp., ISBN 978 9461 055 55 2).